Accounting as a Strategic Tool for Operations in the Tourism Sector - PIRATIH, Ni Made Ayu Mita; MAHARANI, Ni Nyoman Sri Devi; DAMAYANTI, Komang Irma; ASIH, Ni Kadek Astiti (Journal of Tourism Economics and Policy, 2025)
The tourism sector is currently facing significant challenges in enhancing operational efficiency amid intense global competition and dynamic consumer demands. In this context, accounting is no longer viewed merely as a tool for recording financial transactions but as a strategic instrument that provides relevant information to support managerial decision-making. This article aims to explore how accounting can be utilized as a strategic tool in driving operational efficiency within the tourism sector. Through a literature review and case analysis of several tourism entities in Indonesia, this study finds that the implementation of managerial accounting, cost analysis, budget planning, and financial control significantly contributes to improved operational performance. Accurate accounting information enables management to identify areas of waste, optimize resource utilization, and develop innovative strategies to enhance productivity and business sustainability. Furthermore, financial transparency and accountability strengthen stakeholder trust, ultimately having a positive impact on the image and continuity of tourism businesses. These findings emphasize that the integration of effective accounting practices with operational strategies is a key factor in building competitiveness in the tourism sector in the era of globalization. The implications of this study recommend the need to enhance human resource capacity in tourism accounting and to develop more adaptive financial information systems in response to market changes.